IDENTIFIKASI TIPOLOGI FASAD BANGUNAN RUKO PECINAN DI JALAN SEMARANG KOTA MEDAN - Polin DR Naibaho; Isniar Ritonga (LPPM ISTP, 2025)
Construction workers or craftsmen in house building projects are important supporters in building a house or renovating a house. The reality in the field is that many home owners who build houses or renovate, complain about the performance of construction workers who are negligent in their work, causing significant material losses. This research was conducted to look for factors that become obstacles for construction workers in their work process in the field. The research method was carried out in a descriptive qualitative manner. The research location is in the city of Medan in 3 (three) sub-districts, namely Medan Selayang, Medan Tuntungan and Medan Johor. Respondents were divided into foremen, head craftsmen, carpenters, bricklayers and clerks. The results of this research show that the inhibiting factors in the group of internal work relationship factors are: the factor of homeowners who are in high demand. Then the inhibiting factor in the group of external factors in the field is: lack of building materials. Meanwhile, the inhibiting factors for the external environmental factors group are: bad weather factors.